The life of imagination : revealing and making the world - Gosetti-Ferencei, Jennifer Anna (Columbia University Press, 2018)
Imagination allows us to step out of the ordinary but also to transform it through our sense of wonder and play, artistic inspiration and innovation, or the eureka moment of a scientific breakthrough. In this book, Jennifer Anna Gosetti-Ferencei offers a groundbreaking new understanding of its place in everyday experience as well as the heights of creative achievement. The Life of Imagination delivers a new conception of imagination that places it at the heart of our engagement with the world - thinking, acting, feeling, making, and being. Gosetti-Ferencei reveals imagination's roots in embodied human cognition and its role in shaping our cognitive ecology. She demonstrates how imagination arises from our material engagements with the world and at the same time endows us with the sense of an inner life, how it both allows us to escape from reality and aids us in better understanding it. Drawing from philosophy, cognitive science, evolutionary anthropology, developmental psychology, literary theory, and aesthetics, Gosetti-Ferencei engages a spectacular range of examples from ordinary thought processes and actions to artistic, scientific, and literary feats to argue that, like consciousness itself, imagination resists reductive explanation. The Life of Imagination offers a vital account of transformative thinking that shows how imagination will be essential in cultivating a future conducive to human flourishing and to that of the life around us.